Arti Penting Sense of Crisis bagi Humas dan Pimpinan Perguruan Tinggi - Narayana Mahendra Prastya (Jurnal Komunikasi)
No organization is invulnerable towards crisis, including university and/or educational organization. This article aims to give recommendation about the involvement and collaboration between  public relations and the top management in university and/or educational organization, in order to face crisis situation. Crisis situation usually attract media to cover itu. It means, organization should serve the media well, in term giving the information and access to get information. In the other side, media relations activities that usually do by the universities is dominated by making good organization image. Therefore, university’s public relations seems find difficulties when must face the media in crisis situation. Crisis management is the main duty for public relations. But, public relations need support from the top mamangement. In particular situation, representatives from the top manamgement should appear in the media.